Discrepancy between the default and financial distress measured by bankruptcy models - Skerlikova, Tatiana; Rudolfová, Lucie (Journal of Eastern European and Central Asian Research (JEECAR), 2014)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0pt 5.4pt 0pt 5.4pt; mso-para-margin-top:0pt; mso-para-margin-right:0pt; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0pt; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] --> This paper analyzes the discrepancy between the year when a company’s financial problems begin to be measured by bankruptcy models and the year of its default, regardless of the solution (bankruptcy or reorganization). The sample of 50 companies (not traded on financial markets, chosen by turnover, with data available) has been chosen from the list of companies which underwent bankruptcy proceedings in the period 1st January 2008 – 31st August 2013. The timing of the default has been compared to the beginning of financial distress according to the chosen models and the ability of the models to predict the default has been examined. The main objective of this study is to determine how long these not traded companies postpone filling. Our objective is to find out if the companies commence insolvency proceedings in accordance with their impaired financial situation measured by the standard formulas for predicting bankruptcy or if there is any delay. We have found out that companies defer commencement of insolvency proceedings measured by bankruptcy models at least for 2 years. Moreover we conclude that even debtors are not successful with their insolvency petition at their first attempt. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0pt 5.4pt 0pt 5.4pt; mso-para-margin-top:0pt; mso-para-margin-right:0pt; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0pt; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->